Adoption of dairy feed technology and its impact on smallholder farmers' income and poverty in Kenya's south-western region - Vincent Ngeno (Scientific African, 2024)
In south-western Kenya, smallholder dairy farmers use pasture to produce milk from lactating cows, and pasture-based diets are generally less nutritious and yield less milk than improved dairy feed. However, no empirical studies have examined how improved dairy feed technologies affect smallholder dairy farmers' households' welfare or the factors that influence their adoption intensity. Using a double-hurdle model, this study examined the factors affecting and extent of adoption of improved dairy feed, a homemade ration for dairy cattle among 789 smallholder dairy farmers in Bomet county in the south-west region of Kenya, and homemade rations are formulated from feed resources that are readily available on the farm or that can be purchased at a cheap price. In addition, using the propensity score matching (PSM) method, the study examined the causal effects of improved dairy feed on milk income and poverty rates. According to the results, farmers use a lower amount of improved feed than what's technically recommended. By adopting improved feed technologies, dairy farmers in the study area have increased their incomes and decreased their poverty. In addition, dairy income will increase from US$2.87 to $3.39 as a result of better feed adoption. Poverty will decrease by 13 to 32 percentage points as a result. It is important to implement complementary factors to encourage adoption and intensity of this technology, such as improving education, providing extension services, and providing credit facilities, as well as expanding dairy farming areas and lowering the cost of improved feed.